Landscapes of the Jihad: Militancy, Morality, Modernity By Faisal Devji (Ithaca, New York: Cornell University Press, 2005. 164 pages.) (American Journal of Islam and Society, 2007)
In recent years, more has been written about jihad than any other single topicrelated to Islam. Faisal Devji tries to shed light on the people behind the slogans, documents concerning terrorism, and their inner logic by analyzing thewritings, interviews, and communiqués of Osama bin Laden and Ayman al-Zawahiri, as well as the will of Muhammad Atta (pp. 113-15). These andother illustrations clearly reflect the ideological viewpoint of the “jihadists.”This book, an interesting historical and cultural analysis of the so-called“jihadi” movement and its representatives today, focuses on the globalizationof jihad’s moral and aesthetic dimensions. The author deals with its conceptuallandscapes, namely, al-Qaeda’s models of belief and action. In his preface,Devji suggests that both the 1998 terror attacks against the Americanembassies in Dar al-Salaam and Nairobi and 9/11, all undertaken by al-Qaeda, turned jihad into a global weapon of spiritual conflict. Thus, its focushas extended far beyond its original struggle against the Soviet occupation ofAfghanistan. Devji explains: “Two factors make the Jihad into a globalmovement: the failure of local struggle and the inability to control a globallandscape of operations by the politics of intentionality” (p. 31) ...